2006
DOI: 10.1097/01.iop.0000217710.09941.10
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Comparison of Autologous Fat Processing Methods

Abstract: Of the various processing techniques currently used during autologous fat transfer, sedimentation appears to yield a higher proportion of viable adipocytes than does washing or centrifuging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 46 publications
1
24
0
1
Order By: Relevance
“…26 The use of noncentrifuged, gauzestrained liposuctioned fat has been described in the treatment of post-traumatic enophthalmos in sighted, poorly sighted, and anophthalmic orbits, using a sharp 14-gauge needle in the intraconal space. 27 Rose et al 28 have suggested that sedimentation of harvested fat offers improved adipocyte viability over that which is processed by centrifuge or washing. In the absence of evidence of advantageous long-term clinical outcomes, and despite being a more time-consuming procedure, this may prove a useful alternative to centrifuged fat.…”
Section: Volume Augmentation With Autologous Micro-fat Graftmentioning
confidence: 99%
“…26 The use of noncentrifuged, gauzestrained liposuctioned fat has been described in the treatment of post-traumatic enophthalmos in sighted, poorly sighted, and anophthalmic orbits, using a sharp 14-gauge needle in the intraconal space. 27 Rose et al 28 have suggested that sedimentation of harvested fat offers improved adipocyte viability over that which is processed by centrifuge or washing. In the absence of evidence of advantageous long-term clinical outcomes, and despite being a more time-consuming procedure, this may prove a useful alternative to centrifuged fat.…”
Section: Volume Augmentation With Autologous Micro-fat Graftmentioning
confidence: 99%
“…1,2 In 1895, Czerny first described fat grafting for breast reconstruction to improve lumpectomy defects. 3 However, fat grafting lacked widespread acceptance secondary to a high incidence of fat necrosis and cumbersome techniques for tissue transfer.…”
mentioning
confidence: 99%
“…Different processing methods significantly correlated with neither viable adipocytes rates nor grafts longevity (Sommer & Sattler, 2000), while other works (Rose et al, 2006) found that sedimentation was associated to almost double the mean concentration of intact cells than centrifugation (3,000 rpm for 3 min) with or without washing. The limit of almost all these in vitro studies is the assumption that morphologically intact cells are viable and that viable adipocytes rate correlates to graft survival.…”
Section: Fat Processingmentioning
confidence: 73%